Analysis of Liver Histology Several Fish in the Air Kotok River in the Gold Mining Area, Lebong Regency - Lestari, Dian Fita; Febrianti, Eliza; Wulansari, Shahnaz Sabrina; Putra, Apriza Hongko (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2023)
Fish have habitats that are easily exposed to contamination from the environment such as heavy metal waste which can cause changes in the structure and function of body tissues. One type of waste that enters the river in the Lebong Regency River is gold mining processing waste that uses mercury and cyanide. Heavy metals can enter organisms and accumulation and biomagnification of mercury can occur in the bodies of aquatic biota such as fish. There has been no research related to fish histology in the Lebong gold mining area, so the aim of this research was to determine the histological condition of the liver organs of several fish in the form of Hemibagrus nemurus, Rasbora sp, Trichogaster trichopterus, and Macrognathus circumcinctus in the Air Kotok river in the gold mining area of Lebong Regency. The research was conducted using the paraffin method with hematoxylin-eosin staining. Data were analyzed descriptively qualitatively based on the histology of the fish liver. The results of the research on the liver histology, it shows damage to the fish liver structure which includes vacuolization, congestion, pyknosis, dilated sinusoids, melanomacrophages and leukocyte infiltration. The damage to the hepatocytes of this fish can be used as a bio-indicator of exposure to toxic substances in the Air Kotok river, one of which is heavy metal activity from gold mining, which can be a threat to the health and survival of the fish.Keywords: Bengkulu, gold mining waste, heavy metal, hepa